Introduction of New Vaccines: Decision-making Process in Bangladesh - Uddin, Jasim; Sarma, Haribondhu; Bari, Tajul I; Koehlmoos, Tracey P (Journal of Health, Population and Nutrition, 2013)
The understanding of the decision-making process in the introduction of new vaccines helps establish why vaccines are adopted or not. It also contributes to building a sustainable demand for vaccines in a country. The purpose of the study was to map and analyze the formal decision-making process in relation to the introduction of new vaccines within the context of health policy and health systems and identify the ways of making decisions to introduce new vaccines in Bangladesh. During February-April 2011, a qualitative assessment was made at the national level to evaluate the decision-making process around the adoption of new vaccines in Bangladesh. The study population included: policy-level people, programme heads or associates, and key decision-makers of the Government, private sector, non-governmental organizations, and international agencies at the national level. In total, 13 key informants were purposively selected. Data were collected by interviewing key informants and reviewing documents. Data were analyzed thematically. The findings revealed that the actors from different sectors at the policy level were involved in the decision-making process in the introduction of new vaccines. They included policy-makers from the ministries of health and family welfare, finance, and local government and rural development; academicians; researchers; representatives from professional associations; development partners; and members of different committees on EPI. They contributed to the introduction of new vaccines in their own capacity. The burden of disease, research findings on vaccine-preventable diseases, political issues relating to outbreaks of certain diseases, initiatives of international and local stakeholders, pressure of development partners, the Global Alliance for Vaccines and Immunization (GAVI) support, and financial matters were the key factors in the introduction of new vaccines in Bangladesh. The slow introduction and uptake of new vaccines is a concern in the country. Rapid action on the application of GAVI support and less time taken by the Government in processing the implementation and administrative work may expedite the introduction of new vaccines in future in this country. J HEALTH POPUL NUTR 2013 Jun; 31(2): 211-217 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16385